Biological treatment in atypical forms of psoriasis: case reports - Rogowski-Tylman, Michał; Lesiak, Aleksandra; Sysa-Jędrzejowska, Anna; Brucka-Stemkowska, Anna; Sobolewska, Dorota; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Psoriasis is a chronic disease with multiple immune disturbances. The introduction of biologics as therapeutic options for psoriasis vulgaris and psoriatic arthritis became a milestone. However, atypical forms of psoriasis, i.e. generalized pustular psoriasis, psoriasis inversa, scalp psoriasis and palmo-plantar psoriasis, cause many therapeutic difficulties. Although these indications are off-label, there are data in the literature on the use of biological therapy in these forms of psoriasis. Objective. The aim of the study is to present 3 cases of atypical psoriasis treated with biological drugs. Case report. Case 1 – a 24-year-old woman with palmo-plantar psoriasis resistant to therapy with etanercept, adalimumab and ustekinumab; case 2 – a 54-year-old woman with generalized pustular psoriasis effectively treated with infliximab; and case 3 – a 27-year-old man with recalcitrant psoriasis in atypical localization in whom a satisfactory response to adalimumab was observed. Conclusions . The presented case reports as well as literature data indicate that biological treatment might be used alternatively in the treatment of atypical forms of psoriasis.